The Energy Dynamics Of Decentralization From 2004 To 2020 - Achmad, Mansyur; Ashariana, Ashariana (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2020)
Abstract The purpose of this research article is to find out the dynamics of decentralization from 2004 to 2020. Using research data archiving on SCOPUS sources, with a focus on decentralization. The results of this study found that the dynamics of decentralization in the perspective of research from 2004 to 2020 showed increasing numbers, with the use of 16 languages ​​used in the document. The implication of this research increase is the increase in the type of document in the type of publication. Recommendations in this decentralized research require further research in the relationship to the regions in a country. Keywords : Decentralization, Dynamics and Energy